Development of Learning Media Assisted by Geogebra and Interactive Games on Cone Material - Muazarah, Salma Farihah; Qohar, Abd.; Sisworo, Sisworo (Universitas Negeri Semarang, 2025)
The swift advancement of technology offers significant opportunities for the field of education. Technological progress serves as a tool to facilitate teaching and learning processes. One notable application is in the selection of learning media, which plays a crucial role in ensuring that educational activities align with current needs. The aim of this study is the researcher will develop learning media assisted by Geogebra and Interactive Games that are valid, practical, and effective on cone material. This study utilizes a research and development (R&D) approach, applying Thiagarajan’s 4-D model. The participants consisted of 26 students from class IX-B at the Laboratory Junior High School of Malang State University. The findings revealed that the media's validity scored an average of 80%, categorizing it as